2016
DOI: 10.1007/s00253-016-7871-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low pH start-up on continuous mixed-culture lactic acid fermentation of dairy effluent

Abstract: Mixed-culture fermentation that does not require an energy-intensive sterilization process is a viable approach for the economically feasible production of lactic acid (LA) due to the potential use of organic waste as feedstock. This study investigated mixed-culture LA fermentation of whey, a high-strength organic wastewater, in continuous mode. Variations in the hydraulic retention time (HRT) from 120 to 8 h under different pH regimes in two thermophilic reactors (55 °C) were compared for their fermentation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…As to the effect of the HRT variation, it could be observed that the adoption of lower values did not strongly affect the lactic acid concentration. As reported in a previous study [38], when low HRTs were adopted (12 h and 8 h), it was possible to reach a high extracted lactic acid mass in the presence of low lactic acid concentrations. HRT variations affected both the yield and the lactic acid productivity.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…As to the effect of the HRT variation, it could be observed that the adoption of lower values did not strongly affect the lactic acid concentration. As reported in a previous study [38], when low HRTs were adopted (12 h and 8 h), it was possible to reach a high extracted lactic acid mass in the presence of low lactic acid concentrations. HRT variations affected both the yield and the lactic acid productivity.…”
Section: Discussionsupporting
confidence: 63%
“…Different studies demonstrate that the optimum pH value for lactic acid production is between 5.5 and 5.9 [13,39,40]. The adoption of lower values led to low lactic acid concentrations (below 5 g/L) [14,31,38]. In contrast, the results achieved in this study showed that it was possible to produce a high lactic acid amount (20.1 g/L) at low pH, under the adopted uncontrolled pH conditions.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…As a typical bacterial probiotic strain, Bacillus coagulans can produce lactic acid and has an ability in the sporulation to overcome harsh stresses, which can inhibit the growth of intestinal pathogens and regulate the animal intestinal micro-ecological balance (Riazi et al 2009, 2012), and promote animal digestion, and improve animal immunity (Grata and Nabrdalk 2012; Kodali and Sen 2008). Choi et al (2016) reported that the mixed-culture is a viable approach for the economically feasible production of lactic acid due to the potential use of organic waste for B. coagulans as feedstock.…”
Section: Introductionmentioning
confidence: 99%